The Availability of Blue Ocean Strategy Indicators In the Small and Medium Enterprises in Riyadh: Applied Study - Alswied, Mohammed; Alqarni, Ahmed (The Arab Journal of Administration, 2020)
The study aims to identify the availability of blue ocean strategy indicators in the small and medium enterprises in Riyadh. In order to achieve these objectives, the analytical descriptive method was used, and the questionnaire was used to collect data from the study sample, which included (80) respondents of the owners of small and medium enterprises in Riyadh city. The study results showed that the availability of blue ocean strategy indicators (combined) in the small and medium enterprises in Riyadh was with a high degree. Also, the study results showed that the (Raising) indicator has attracted the interest of the small and medium enterprises in the city of Riyadh, where it ranked first, followed by the (Elimination) indicator, followed by the (Reduction) indicator, then the (Creation) indicator came in the last. The researcher also found that there were no significant differences at the level of significance (0.05) in respondents’ responses to the availability of blue ocean strategy indicators in the small and medium enterprises in Riyadh city due to the following variables: (project size depending on capital, years of establishment, project activity), while differences were found in the availability of the (Reduction) indicator, and in the blue ocean strategy indicators (combined) due to a variable of (project size depending on labor), and in favor of a small project category (the number of employees ranges between 6 to 50 workers).